(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
With the increase in the technology of weapon system, there is great revolution in the concept of warfare. Technology as a force multiplier provides cutting edge and competitive in modern warfare. Modern warfare requires autonomous weapons. In the new era, missiles are known as the strength for a country. For a modern military inventory, guided weapons technology is a prerequisite. From very short range to short, medium and long range weapons and automated weapons are the topic for research. In this paper, a critical study is carried on different types of missiles and their classification based on their features like target, range, mode for launching and their autopilot guidance system.